Internet of Things and Cloud Computing Integration of Opera Elements into Vocal Singing Teaching Practice Exploration - Li, Gang (EAI Endorsed Transactions on Scalable Information Systems, 2023)
INTRODUCTION: With the rapid development of computer technology, the application of the Internet of Things and cloud computing technology is becoming more and more common. However, there is no more computer technology integration in integrating opera elements into vocal singing teaching. Therefore, compared with other industries, the development of verbal singing teaching could be faster and adapt to the current era of the Internet of Things and cloud computing. Thus studies the exploration of the practice of integrating opera elements into vocal singing teaching based on the Internet of Things and cloud computing. OBJECTIVES: To improve the level of China’s Internet of Things and cloud computing technology-based opera elements into vocal singing teaching practice; to solve the current problem of China’s traditional culture not being integrated into verbal singing teaching; to promote the development of China’s opera industry, the modernization of oral singing teaching, and to enhance the relevance of the Internet and economic development. METHODS: In the study, firstly, the Internet of Things (IoT) and cloud computing technology are used for the establishment of the evaluation model; secondly, the feasibility of integrating opera elements into vocal singing teaching is analyzed through theoretical discussions; lastly, through the analysis of the model of the Internet of Things (IoT) and cloud computing, the feasibility of integrating opera elements into vocal singing teaching is illustrated by the analysis of the model of the Internet of Things (IoT) and cloud computing, and how the Internet of Things and cloud computing can assist opera elements to be integrated into vocal singing teaching. RESULTS: Using the Internet of Things and cloud computing technology to enrich the vocal singing teaching model from multiple perspectives can better enhance the integration of opera elements into verbal singing teaching. Internet of Things and cloud computing technology play an auxiliary role in the integration of opera elements into vocal singing teaching; the study of the additional mechanism reveals that the effect of the integration of opera elements into verbal singing teaching can be improved through the improvement of the means of the auxiliary function. CONCLUSION: As a representative of Chinese culture, the integration of opera elements into vocal singing teaching practice is of great significance, and the Internet of Things and cloud computing technology play an essential role in helping the integration of opera elements into vocal singing teaching practice.